The touch of the present : educational encounters, aesthetics, and the politics of the senses - Todd, Sharon, 1962- (State University of New York Press, 2023)
Explores the importance of the body and the senses in educational encounters, drawing out the aesthetic and political dimensions of educational practices.
Keywords: Human body in education.; Learning, Psychology of.; Senses and sensation.; Spatial behavior.; Intersubjectivity.; Liminality.; Psychologie de l'apprentissage.; Sens et sensations.; Intersubjectivité.; Liminalité.; EDUCATION / Philosophy, Theory & Social Aspects.; Human body in education; Intersubjectivity; Learning, Psychology of; Liminality; Senses and sensation; Spatial behavior; Electronic books.